Orang-Orang Yang Berhak Menerima Warisan - Robi’ah, Rob'iah; Nuriyati, Tuti; Roinah, Roinah (Universitas Pakuan, 2026)
People Who Are Entitled To Receive InheritanceThis article comprehensively discusses the concept of inheritance in Islam, focusing on the categories of people entitled to receive inheritance and their legal basis. This study uses a qualitative method through literature review to analyze the provisions of faraidh, the pillars and conditions of inheritance, the causes of obtaining and losing inheritance rights, and the hijab mahjub system that regulates the priority of heirs. The discussion includes the classification of heirs according to Islamic jurisprudence, namely ashab al-furudh, ashabah, and dzawu al-arham, along with the inheritance distribution mechanism determined by sharia through the Qur'an and hadith. In addition, the study examines the pluralism of inheritance law in Indonesia, which includes Islamic law, positive law (KHI and Civil Code), and customary law. The results of the study indicate that inheritance distribution in Islam is detailed, proportional, and aims to maintain family justice, while its application in Indonesia must consider the diversity of applicable legal systems. This study provides an in-depth understanding of the structure of inheritance, the principles of hijab mahjub, and the relevance of the application of faraidh law in the Indonesian socio-legal context.